The contested relationship between paid work and women’s empowerment: Empirical analysis from Bangladesh - Kabeer, Naila; Mahmud, Simeen; Tasneem, Sakiba (Springer Link, 2022)
This article was published in The European Journal of Development Research [Copyright © 2018, European Association of Development Research and Training Institutes (EADI)] and the definite version is available at: https://doi.org/10.1057/s41287-017-0119-y The Article's website is at: https://link.springer.com/article/10.1057/s41287-017-0119-y#citeas